Cobalt‐Catalyzed Regioselective Hydroboration of Terminal Alkenes. Issue 38 (16th October 2017) - Zhang, Guoqi; Wu, Jing; Wang, Man; Zeng, Haisu; Cheng, Jessica; Neary, Michelle C.; Zheng, Shengping
Abstract : Cobalt(II) catalysts based on flexible PNP or NNN ligands were explored for the regioselective hydroboration of alkenes. A known Co II –PNP pincer complex was found to efficiently catalyze alkene hydroboration with excellent anti‐Markovnikov selectivity, whereas a newly synthesized dinuclear Co II –NNN complex was found to catalyze the hydroboration of a range of aromatic terminal alkenes with good Markovnikov selectivities (up to 98:2, b/l). This represents a rare example of Markovnikov selectivity in the hydroboration of alkenes using an inexpensive, flexible‐ligand‐supported dinuclear cobalt catalyst. Abstract : Cobalt(II) catalysts based on flexible PNP or NNN ligands were found to catalyze the regiodivergent hydroboration of alkenes. A new dinuclear Co II –NNN complex catalyzes the hydroboration of a range of aromatic terminal alkenes with good Markovnikov selectivity. This represents a rare example of Markovnikov selectivity in the hydroboration of alkenes using an inexpensive dinuclear cobalt catalyst.